2006
DOI: 10.1007/s11162-006-9022-7
|View full text |Cite
|
Sign up to set email alerts
|

Legal issues and statistical approaches to reverse pay discrimination in higher education

Abstract: There have been numerous lawsuits within higher education brought by females over pay inequity and many articles have been written on the topic. Although not as prevalent, there have been some recent instances where male faculty have claimed-with some degree of success-that the process used by their institutions to make salary adjustments for females was unfair and led to reverse pay discrimination. In this paper, we examine some of the legal issues and statistical approaches surrounding claims of reverse sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some administrators may fear that any salary adjustments explicitly based on such studies would be an invitation for additional complaints from aggrieved parties (i.e., male faculty). However, analysts have suggested that across-the-board adjustments are less likely to promote additional disputes (Eckes & Toutkoushian, 2006). Regardless of the approach, it would be possible to have a phased plan whereby some degree of progress might be assured over a designated time period, for example, a $1,000 increment across-the-board to women in each of 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some administrators may fear that any salary adjustments explicitly based on such studies would be an invitation for additional complaints from aggrieved parties (i.e., male faculty). However, analysts have suggested that across-the-board adjustments are less likely to promote additional disputes (Eckes & Toutkoushian, 2006). Regardless of the approach, it would be possible to have a phased plan whereby some degree of progress might be assured over a designated time period, for example, a $1,000 increment across-the-board to women in each of 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations to remedy gender-based salary inequity have evolved over time in light of research findings and in response to legal challenges and outcomes of litigation over gender-based pay inequity and pay discrimination. When gender-based pay inequities are found, salary adjustments can be made both across the board and individually (Eckes and Toutkoushian, 2006). Other strategies for salary inequity focus on prevention by examining pay differentials at time of hiring.…”
Section: Augmenting Infrastructures and Organizational Normsmentioning
confidence: 99%